The modern X-ray imaging manners for diagnosis of the dental diseases (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The Medical imaging procedures that help radiologists diagnose and treat health conditions showed a clear and exact description of the structure changes. There are many devices, apparatus, and technologies used in the medical field, such as x-ray applications which include computed tomography (Ct) Scanner, Tuned Aperture Computed Tomography (Tact), Cone Beam Computed Tomography (Cone). Recent medical imaging technologies have been used in tooth disease diagnostics for treatment purposes. The New x-ray Techniques can detect dental diseases and determine any structure changes for therapeutic purposes. These technologies help reduce morbidity and mortality and improve the quality of life. Our review sheds light on modern and modern techniques in the applications of x-ray technology in dentistry. It sheds light on some details related to it, such as the uses of x-rays and the risks of radiation in adults and children and the components and types of devices that make up these rays, especially those used in dentistry, in addition to a historical overview starting from Before the discovery of Roentgen.